INTERPRETATIONS ON THE EXPRESSION OF GENDER-SPECIFIC STEREOTYPES IN THE SPEECH BEHAVIOR OF INTERNET USERS (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes some considerations on the manifestation of gender stereotypes in the speech behavior of Internet users. These views emphasize the importance of the role of men in overcoming stereotypes and the importance of involving men in the process of change, overcoming gender stereotypes is a global problem, and international cooperation, exchange of successful practices, coordinated actions of different countries, and taking into account cultural characteristics are of great importance.